Narrating the Heritage of Psychiatry - Punzi, Elisabeth,; Singer, Christoph,; Wächter, Cornelia, (Literature and Cultural Studies E-Books Online, Collection 2025., 2024)
This volume highlights the importance of diverse voices and perspectives in understanding the history and heritage of psychiatry. Exploring the complex interrelations between psychiatry, heritage and power, Narrating the Heritage of Psychiatry c